2021
DOI: 10.14366/usg.20147
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness quantification in biopsy-proven nonalcoholic fatty liver disease patients using shear wave elastography in comparison with transient elastography

Abstract: This study prospectively assessed the performance of liver stiffness measurements using point shear-wave elastography (p-SWE) in comparison with transient elastography (TE) in patients with biopsy-proven nonalcoholic fatty liver disease (NAFLD). Methods: Fifty-six consecutive adult patients with a histological diagnosis of NAFLD prospectively underwent TE and p-SWE on the same day. The median of 10 measurements (SWE-10), the first five (SWE-5), and the first three (SWE-3) measurements were analyzed for p-SWE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…15 While recent studies have examined diagnostic performance of SWE methods in chronic liver disease, most have either utilized point SWE instead of 2D-SWE and/or included participants with a diverse range of liver disease etiologies. [15][16][17][18][19][20][21][22][23][24][25] Data on disease-specific accuracy and cutoff values of 2D-SWE for staging hepatic fibrosis in adults with NAFLD, 26 especially when compared with VCTE, [27][28][29] are limited.…”
Section: Introductionmentioning
confidence: 99%
“…15 While recent studies have examined diagnostic performance of SWE methods in chronic liver disease, most have either utilized point SWE instead of 2D-SWE and/or included participants with a diverse range of liver disease etiologies. [15][16][17][18][19][20][21][22][23][24][25] Data on disease-specific accuracy and cutoff values of 2D-SWE for staging hepatic fibrosis in adults with NAFLD, 26 especially when compared with VCTE, [27][28][29] are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Taibbi et al showed that the diagnostic performances of shear wave elastography (SWE) 10, SWE 5, and SWE 3, compared with TE, had no significant difference in both significant and advanced fibrosis. However, it was higher for SWE 5 and SWE 10 [15]. Sharpton et al found the diagnostic accuracy for detecting fibrosis lower for 2D SWE compared to VCTE, and this finding was particularly highlighted in those with higher BMI [20].…”
Section: Discussionmentioning
confidence: 97%
“…Liver fibrosis is one of the strong predictors of clinical outcomes in patients with NAFLD [33,34] . Recently, a systematic review claimed that liver fibrosis could also be found in general population with the prevalence of 1% to as high as 26% [9] .…”
Section: Discussionmentioning
confidence: 99%